Cote d'Ivoire : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Cote d'lvoire adopted an IMF-supported program in early 1994 following the devaluation of the CFA franc. Under this program, progress was made in reducing financial imbalances, controlling inflation, liberalizing the economy, and establishing a sound basis for sustainable economic growth necessary to reduce poverty. The following statistical data are also presented: selected national accounts indicators, GDP by origin, deflators of sectoral output, price structure of oil and gas products, production and exports of lumbar, export prices and costs of cocoa and coffee, and producer prices in agriculture.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet